Utilizacion de raices y productos de yuca en alimentacion animal - Gómez G., G.; Santos Núñez, Jorge; Valdivieso Garcia, Mauricio A. (International Center for Tropical Agriculture, 1983)
Information on the nutritional quality of cassava roots and leaves (chemical composition, root HCN content) and the use of these products in nutrition programs for domesticated animals, especially poultry and pigs, is reviewed. In feeding trials no differences were found regarding the production of broiler chicks fed rations containing similar levels of CM from either bitter or sweet var. Broiler chicks consumed greater quantities of rations with 20 and 30 percent CM compared with rations containing 10 percent. Recent results with CM-based rations for in-pig and nursing sows and for growing pigs indicate that under normal conditions it is not necessary to add met. in higher amounts than those needed to meet normal requirements. Piglets preferred and consumed greater amounts of rations containing 40 percent CM than rations containing 20 percent CM. The feasibility of efficiently using CM and sugar cane molasses an basic ingredients to totally substitute ceral grains was proven; however, the amount of soybean cake required as protein supplement is greater. Cassava forage production represents the highest potential of utilization ofcassava in ruminant nutrition. Yields more than 30 t can be obtained throughout the yr by increasing the no. of plants/ha to 111,000 with a spacing of 30 cm x 30 cm and 4 cuttings/yr of the whole plant canopy. Tables are included on the chemical composition of cassava products and the results of poultry and swine feeding programs. (CIAT)